FRI0184 A Snapshot of Contemporary Urate-Lowering Therapy (ULT) Care and Serum Uric Acid (SUA) Monitoring in A US Commercially-Insured Gout Population. (10th June 2014) - Ramachancran, S.; Morlock, R.; Horne, L.; Kern, D.M.; Tunceli, O.; Zhou, S.; Choi, H.K.
Abstract : Background: Gout is the most common inflammatory arthritis in most western countries and is caused by hyperuricemia. The reduction of gout symptoms, as well as the reduction and maintenance of sUA levels ≤6 mg/dL, is a commonly recommended treatment goal for gout patients. Objectives: To provide a snapshot of contemporary ULT care, sUA monitoring, and associated costs in the US commercially-insured gout population. Methods: Gout patients treated with ULT were identified between 1 Feb 2011 and 31 Jan 2012 from the HealthCore Integrated Research Environment. The index event was considered to be the earliest of the following events: a prescription for ULT, a diagnosis of gout (ICD-9 274.xx), or a claim for colchicine with ULT therapy in the year prior. Patients with <12 months pre- and post-index enrolment or with a diagnosis of cancer were excluded. Patient demographics and comorbidities were captured in the 12 month pre-index period. Treatment characteristics, sUA laboratory tests, overall gout control (defined as: sUA ≤6 mg/dL, no flares, and no tophi), and costs were examined during the 12 month post-index period. Flares were defined during the post-index period as either a claim for colchicine, or a healthcare visit recording gout together with at least one of the following treatment patterns within 1 week: joint aspiration or injection (corticosteroids), prescription of NSAIDs, corticosteroids, adrenocorticotropic hormone, or IL-1 antagonist. Results: 50, 602 ULT-treated patients met the inclusion criteria, including 29% new ULT users. The average age was 59, and 82% were male. During follow-up, 90% of patients received allopurinol, 6% received febuxostat, and 4% received probenecid. Comorbidities were common, including hypertension (70% of patients), hyperlipidemia (61%), and diabetes (30%). Most patients had prior ULT use (71%), while the rest initiated ULT treatment on the index date. Use of acute gout care drugs consisted of colchicine (18%), NSAIDs (32%), and corticosteroids (22%). Overall, 46% of patients had at least 1 sUA laboratory test during the one-year follow-up period. Within the subset of patients with available sUA results (n=6, 649), 47% of subjects had sUA levels ≤6 mg/dL and 30% had achieved overall gout control. For the overall study population, average all-cause costs were $11, 804. Those with 0 flares had the lowest average all-cause costs ($11, 212), while those with 1-3 ($12, 615) and >3 flares ($15, 276) had higher average costs. Furthermore, among prevalent ULT users, average costs were lower in those who attained overall gout control compared with those who did not ($11, 430 vs. $12, 596). Conclusions: This study of contemporary ULT-treated gout patients confirms that their levels of comorbidities are high, especially hypertension and hyperlipidemia. Further, among patients who had used ULT prior to index, those who attained overall gout control had lower total costs than those who did not. The overall sUA goal was met in less than half of the population, and only 30% attained overall gout control. These findings suggest that contemporary gout care remains suboptimal, leaving considerable room for improvement. Disclosure of Interest: S. Ramachancran Employee of: AstraZeneca, R. Morlock Employee of: Ardea Biosciences, L. Horne Employee of: AstraZeneca, D. Kern Employee of: HealthCore, O. Tunceli Employee of: HealthCore, S. Zhou Employee of: HealthCore, H. Choi: None declared DOI: 10.1136/annrheumdis-2014-eular.1769